Design and Development of Physical Education Curriculum - Wisata, I Ketut; Setiawan, I Made Abdi; Gotama, Made Restu; Munegara, I Made Era Junva; Putra, I Kadek Nuprianta (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to determine the definition of curriculum and the design of physical education curriculum development. The curriculum is an important part of an educational process. Because education without a curriculum will look chaotic and irregular. This will cause changes in curriculum development, especially in Indonesia. The curriculum is one of the tools to achieve educational goals, and is also used as a guideline in the implementation of the teaching and learning process in various types and levels of schools. This study uses a descriptive qualitative method. This study applies secondary data, where this data is obtained from various sources in the form of books and journals that are still related to the title of the study, because this type of research is a literature study. The researcher will describe and explain in detail the definition of curriculum and the design of physical education curriculum development. The Physical Education (Penjas) curriculum design is a structure and learning design designed to develop students' physical, mental, social, and emotional aspects through physical activity. The Penjas curriculum design usually includes several key components, such as learning objectives, material content, learning methods, and evaluation. The main elements that are usually found in the Penjas curriculum design are; Learning Objectives, Learning Materials, Learning Strategies and Methods, Learning Evaluation, Attitude and Character Development.